2016
DOI: 10.1186/s40798-016-0060-1
|View full text |Cite
|
Sign up to set email alerts
|

Fat Utilization During High-Intensity Exercise: When Does It End?

Abstract: BackgroundThis study examined substrate oxidation at high-intensity exercise and aimed to determine when fat oxidation ends (FATmin). We hypothesized the existence of a connection between the anaerobic threshold (AnT) and FATmin point.MethodsBreath-by-breath data obtained from indirect calorimetry during a graded treadmill test were used to measure substrate oxidation and maximal oxygen uptake (VO2max) on 47 males (30 athletes (ATL) and 17 non-athletes (NATL)). Pearson correlation coefficient (r) and effect si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 26 publications
2
20
2
Order By: Relevance
“…Existence of high correlation between FAT min and AnT found in our study ( r = 0.99, p < 0. 01) is in line with previous studies performed on athletes and sedentary subjects where short test stages and VT were used [7,8,15]. It is believed that an increased lactate production in specific muscles and intra-muscles hypoxic conditions at intensities at/above AnT impedes lipolysis directly contributing to this phenomenon [24,28].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Existence of high correlation between FAT min and AnT found in our study ( r = 0.99, p < 0. 01) is in line with previous studies performed on athletes and sedentary subjects where short test stages and VT were used [7,8,15]. It is believed that an increased lactate production in specific muscles and intra-muscles hypoxic conditions at intensities at/above AnT impedes lipolysis directly contributing to this phenomenon [24,28].…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, direct comparisons with previous studies are difficult due the differences in testing methodology and subjects’ characteristics [9,20]. In our study, FAT min was found to be at 53.40 % of VO 2max (range 49.40 to 62.52), which is lower than previous studies performed on athletic and sedentary men [3,7,8]. However, sedentary and adipose subjects cease to oxidize fat at lower exercise intensities due to weak aerobic and cardiorespiratory fitness [3,21].…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Lactate accumulation during exercise is acutely related to a decrease in fat oxidation ( Achten & Jeukendrup, 2004 ; Bircher & Knechtle, 2004 ; González-Haro et al, 2007 ). Besides, Peric et al (2016) have suggested a high correlation between anaerobic threshold and minimum fat oxidation. In this study, the lactate levels of all participants may be explained with this relationship.…”
Section: Discussionmentioning
confidence: 99%